PERSAMAAN DAN PERBEDAAN MAKNA DAN FUNGSI RUIGIGO VERBA KITAI SURU DAN KIBOU SURU DALAM KALIMAT BAHASA JEPANG - Kusuma, Nila Candra (Jurnal Ilmiah Mahasiswa FIB, 2013)
Japanese language have many synonym, for example verbs kitai suru and kibou suru that have similar meaning ‘hope’. Those verbs frequently appear in text books, mass media, or Japanese songs. But, because there is no many explanation about the way to use it in any translation dictionary, it can made confused. The purpose of this study is to knowing about verbs kitai suru and kibou suru’s another meaning and function to found the difference way to use it.  The research method that used is descriptive qualitative analysis. The data that used is from The Asahi Shimbun year edition 2003 and 2004,  and Nipponia magazine edition number 45 year 2008 June 15th that contains those verbs. The result is those verbs have similar meaning ‘hope’, ‘wish realization’, and ‘wish good prospect in the future’. The difference is verb kitai suru have another meaning hope to winning in some competition. Meanwhile, verb kibou suru is used just for hope some good thing. Those verbs can be substituted if there is similar meaning in some sentence, but can’t be substituted if there is the difference.     Keywords : synonym, verb, kitai suru, kibou suru